Blockchain Technology Use on Transactions of Crypto Currency with Machinery & Electronic Goods - Ganapathy, Apoorva (American Journal of Trade and Policy, 2016)
Blockchain technology used in transactions of cryptocurrency with machinery & electronic goods deals with keeping the transactions secure by using blockchain technology so that machinery and electronic goods can be bought by cryptocurrencies. Currently, there are transactions from cryptocurrency based on blockchain networks that can be done securely. The name is coined from the arrangement of records. Single records are referred to as blocks. They are also connected in a list known as chains. Transactions on the blockchain network can be kept secure. Cryptocurrencies can be used just like the normal centralized currencies for any kind of transaction on the blockchain network.
Keywords: Blockchain; Cryptocurrency; Bitcoin; Hashgraph; Nodes